Catachresis and Mis-Being in Judith Butler and Étienne Balibar: Contemporary Refigurations of the Human as a Face Drawn in the Sand. (30th May 2018) - Ingala, Emma
Abstract: The controversy over humanism in the second half of the twentieth century seemed to promote an irreversible abandonment of the concept of the human, famously illustrated by Foucault's image of the face sketched in the sand at the seashore being erased by the water. In the last two decades, however, a number of philosophers have reassessed and returned to a certain notion of the human all the while incorporating the arguments of the anti-humanist and anti-anthropocentric critiques. Judith Butler and Étienne Balibar are among them. The aim of this article is to explore and compare the particular tropes that both put into play to refigure the human (namely, catachresis in Butler and mis-being in Balibar), and to show how, in light of these tropes, a different reading of Foucault's metaphor emerges; one in which the human is understood as a continuous and tensional process of doing and undoing, of drawing and erasing lines in the sand.